Sagot :
Answer:
1) 5. . 2)-7/2. (3) 0. (4) 11/2 (5) 0. (6). 0
[tex]1) {x}^{2} - 5x + 12 \\ a = 1 \: \: b = - 5 \: \: c = 12 \\ sum \: of \: root = \frac{ - b}{a} \\ sum \: of \:root = \frac{ - ( - 5)}{1} \\ sum = 5[/tex]
question2
[tex] - 2 {x}^{2} - 7x + 4 \\ a = - 2 \\ b = - 7 \\ c = 4 \\ sum = \frac{ - b}{a} \\ sum = \frac{ - ( - 7)}{ - 2} \\ sum = \frac{ - 7}{2} [/tex]
[tex]question3 \\ - 3 {x}^{2} + 4 \\ a = - 3 \: \: b = 0 \: \: c = 4 \\ sum \: of \: root = \frac{ - b}{a} \\ sum = \frac{ - 0}{ - 3} = 0[/tex]
[tex]4)2 {x}^{2} - 5x + 11 \\ a = 2 \: \: \: b = - 5 \: \: \: c = 11 \\ product \: = \frac{ c}{a} = \frac{ 11}{2 } = \frac{11}{2} [/tex]
question 5
[tex]product \: of \: the \: root \: is \: equal \: to \: \frac{c}{a} \\ {x}^{2} + 4x \\ a = 1 \\ b = 4 \\ c = 0 \\ product = \frac{c}{a} = \frac{0}{1} = 0 \\ the \: product \: of \: root \: is \: zero[/tex]
question6
[tex]question6 \\ a {x}^{2} + bx + c \\ - 3 {x}^{2} - 8x \\ here \: a = - 3 \\ b = - 8 \\ and \: c \: not \: available \: \: mean \: that \: \\ c = 0 \\ product \: of \: root \: = \frac{c}{a} = \frac{0}{ - 3} \\ product = 0[/tex]